Crises cambiais e estrutura decisória: a política de recuperação econômica na argentina e no Brasil - Philippe Faucher; Elliott Armijo Leslie (Universidade do Estado do Rio de Janeiro, 2004)
This paper seeks to explain why exchange rate crises of rather similar causes and magnitude can be so much harder for one emerging market country to absorb and bounce back from than for another. Our argument takes three recent currency crises as examples: Argentina (late 2001) and Brazil (early 1999 and mid-2002). We conclude that most of the difference resulted from the structure of domestic political institutions and the incentives for cooperation and conflict that such institutions created for political incumbents and other players.